2015
DOI: 10.1007/s12471-015-0664-y
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guidelines for the prescription of secondary prevention medication at hospital discharge after acute coronary syndrome: a multicentre study

Abstract: BackgroundThe prescription of guideline-recommended medication for secondary prevention after acute coronary syndrome has been suboptimal in the past. In the present study, guideline adherence and associated patient, care and hospital characteristics at hospital discharge after acute coronary syndrome were studied.MethodsCharts of patients with acute coronary syndrome discharged from 13 Dutch hospitals in 2012 were reviewed. Guideline adherence was defined as the prescription of acetylsalicylic acid, P2Y12 rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
3
15
2
Order By: Relevance
“…Previous studies focussing on medication at discharge show a substantial guideline adherence in patients with AMI (65–69% were prescribed all five indicated drugs) [ 25 , 26 ]. Additionally, a recent European guideline evaluation by the EUROASPIRE IV Study Group showed comparable secondary prevention rates at a median follow-up time of 16 months after myocardial infarction: 94% antiplatelets, 86% statins, 83% beta-blockers and 75% ACE inhibitors/AT2 antagonists [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focussing on medication at discharge show a substantial guideline adherence in patients with AMI (65–69% were prescribed all five indicated drugs) [ 25 , 26 ]. Additionally, a recent European guideline evaluation by the EUROASPIRE IV Study Group showed comparable secondary prevention rates at a median follow-up time of 16 months after myocardial infarction: 94% antiplatelets, 86% statins, 83% beta-blockers and 75% ACE inhibitors/AT2 antagonists [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies conducted in the Netherlands, about 65% and 69% of ACS patients were discharged with the guideline-recommended medications for ACS secondary prevention. 20 , 23 The study conducted in Australia and New Zealand also reported that the rate of ACS patients discharged on secondary prevention medications was about 71%. 26 However, this study applied the different definition about an optimal medication therapy for secondary prevention after ACS.…”
Section: Discussionmentioning
confidence: 99%
“…Medical knowledge is advancing at an ever-increasing rate, and clinicians face the challenge of keeping up with all these new advancements. Excessive demands can lead to suboptimal guideline adherence and variation among hospitals [ 25 ]. Clinical decision support systems can help clinicians decide on optimal therapies for their patients on a more personalized basis, incorporating clinical parameters and even genetic data.…”
Section: Discussionmentioning
confidence: 99%